Can the Presence of Endoscopic High-Risk Stigmata be Bredicted before Endoscopy? A Multivariable Analysis Using the RUGBE Database. Issue 6 (2014) - Chen, Yen-I; Wyse, Jonathan; Barkun, Alan; Bardou, Marc; Gralnek, Ian M; Martel, Myriam
Abstract : BACKGROUND: Many aspects in the management of acute upper gastrointestinal bleeding rely on pre-esophagogastroduodenoscopy (EGD) stratification of patients likely to exhibit high-risk stigmata (HRS); however, data predicting the presence of HRS are lacking. OBJECTIVE: To determine clinical and laboratory predictors of HRS at the index EGD in patients presenting with acute upper gastrointestinal bleeding using retrospective data from a validated national database – the Canadian Registry in Upper Gastrointestinal Bleeding and Endoscopy registry. METHODS: Relevant clinical and laboratory parameters were evaluated. HRS was defined as spurting, oozing, nonbleeding visible vessel or adherent clot after vigorous irrigation. Multivariable modelling was used to identify predictors of HRS including age, sex, hematemesis, use of antiplatelet agents, American Society of Anesthesiologists (ASA) classification, nasogastric tube aspirate, hemoglobin level and elapsed time from the onset of bleeding to EGD. RESULTS: Of the 1677 patients (mean [± SD] age 66.2±16.8 years; 38.3% female), 28.7% had hematemesis, 57.8% had an ASA score of 3 to 5, and the mean hemoglobin level was 96.8±27.3 g/L. The mean time from presentation to endoscopy was 22.2±37.5 h. The best fitting multivariable model included the following significant predictors: ASA score 3 to 5 (OR 2.16 [95% CI 1.71 to 2.74]), a shorter time to endoscopy (OR 0.99 [95% CI 0.98 to 0.99]) and a lower initial hemoglobin level (OR 0.99 [95% CI 0.99 to 0.99]). CONCLUSION: A higher ASA score, a shorter time to endoscopy and lower initial hemoglobin level all significantly predicted the presence of endoscopic HRS. These criteria could be used to improve the optimal selection of patients requiring more urgent endoscopy.